2020
DOI: 10.1002/pits.22419
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of teacher self‐efficacy in the relation between teacher–child race mismatch and conflict

Abstract: The far-reaching impacts of the teacher-child relationship, including academic achievement and social/behavioral adjustment, have been well-documented. At the same time, literature also suggests that teacher perceptions of teacher-child relationships are impacted by the race/ethnicity match or mismatch between teacher and child, with matching related to more positive teacher perceptions. However, limited work has focused on children who are at-risk for emotional and behavioral disorders (EBDs) or tested the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…For example Hamre et al (2008) found that teachers with generally low self-efficacy judgments experienced higher degrees of teacher-child conflict than would be expected based on their judgments of these children's problem behaviors. More recent results also concur with this idea, suggesting that teachers who feel less self-efficacious in managing individual children's behaviors in class generally experience more conflict with them (Kunemund et al, 2020;Zee et al, 2017). Thus, based on research on parental and teacher self-efficacy, it seems likely that parents who feel less efficacious in teaching their children will also experience more conflicts with their child during help with schoolwork.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…For example Hamre et al (2008) found that teachers with generally low self-efficacy judgments experienced higher degrees of teacher-child conflict than would be expected based on their judgments of these children's problem behaviors. More recent results also concur with this idea, suggesting that teachers who feel less self-efficacious in managing individual children's behaviors in class generally experience more conflict with them (Kunemund et al, 2020;Zee et al, 2017). Thus, based on research on parental and teacher self-efficacy, it seems likely that parents who feel less efficacious in teaching their children will also experience more conflicts with their child during help with schoolwork.…”
mentioning
confidence: 79%
“…Relevant to homeschooling, a larger sense of parental self-efficacy is associated with less behavioral problems in children (Albanese et al, 2019), which might generalize to parent-child conflicts during parental help with schoolwork as well. Moreover, evidence on teacher self-efficacy suggests that teachers' capability beliefs may affect the quality of teacher-child relationships (e.g., Hamre et al, 2008;Jimmieson et al, 2010;Kunemund et al, 2020;Mashburn et al, 2006;. For example Hamre et al (2008) found that teachers with generally low self-efficacy judgments experienced higher degrees of teacher-child conflict than would be expected based on their judgments of these children's problem behaviors.…”
mentioning
confidence: 99%
“…Teachers can play a crucial role in helping students feel safe, supported, and connected by creating affirming learning environments and positive student relationships. For students of color in urban communities, affirming practices and positive teacher-student relationships can help students cope with personal stressors and serve as a buffer against systemic racism and discrimination ( Ladson-Billings, 1994 ; Sosa & Gomez, 2012). Unfortunately, the unprecedented nature of the COVID-19 pandemic and the resulting personal and professional challenges faced by teachers in urban schools ( Baker et al, 2021 ) may challenge their self-efficacy to support students of color whom the pandemic has most impacted.…”
Section: Introductionmentioning
confidence: 99%
“…I did not find a similar effect for externalizing problem behaviors. Teaching students with internalizing problems can generate uncertainty because it requires a proper understanding of the behavior and its underlying causes, which might be more difficult when teachers and students do not share the same ethnic background (Kunemund et al, 2020;Pigott & Cowen, 2000;Saft & Pianta, 2001). Moreover, the fact that there is not a similar effect for externalizing problem behaviors suggests that dealing with internalizing problems requires more subtle and culturally sensitive pedagogic skills than dealing with externalizing problems (Le Roux, 2002;Wubbels, Den Brok, Veldman, & Van Tartwijk, 2006).…”
Section: Teacher Challenge 1: Teaching Students Of Diverse Cultural Bmentioning
confidence: 99%
“…One implication of this finding is that teachers or educators may want to pay particular attention to improving the dyadic interactions between student and teacher, especially in relationships that are somewhat problematic. Studies have not yet been able to determine if teacher self-efficacy is negatively affected by relational conflict or the other way around (Kunemund et al, 2020;, but I tend to think the affective and efficacy aspects of the relationship develop simultaneously and in mutual interaction. I would, therefore, suggest assessing where and why conflict occurs but also in which domains of teaching a teacher feels less capable.…”
Section: Challenge 1 Teaching a Diverse Student Populationmentioning
confidence: 99%